2014
DOI: 10.1136/vr.102352
|View full text |Cite
|
Sign up to set email alerts
|

Veterinarians' attitudes to chronic pain in dogs

Abstract: Veterinary surgeons in the UK were invited to complete an internet survey concerning their attitudes to chronic pain in dogs. UK veterinary surgeons numbering 215 completed surveys in full along with 48 worldwide specialists in anaesthesia and 37 worldwide specialists in oncology. Osteoarthritis, dental and aural disease, vertebral and spinal cord conditions, neoplasia and skin conditions were considered important causes of chronic pain in dogs. UK practitioners used significantly fewer classes of analgesic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…Approximately 39% of owners indicated that analgesics were not likely needed for ear infections, yet human and veterinary medical professionals consider otitis as a painful condition and attribute pain management of utmost importance . Veterinarians in a British study ranked aural pain as the third most common cause of chronic pain in small animal practices . Because veterinarians identify ear infection as painful, it appears that client education on this condition should be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 39% of owners indicated that analgesics were not likely needed for ear infections, yet human and veterinary medical professionals consider otitis as a painful condition and attribute pain management of utmost importance . Veterinarians in a British study ranked aural pain as the third most common cause of chronic pain in small animal practices . Because veterinarians identify ear infection as painful, it appears that client education on this condition should be improved.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies reporting long term safety are lacking (Innes et al, 2010), and reporting of adverse events may be incomplete, both in clinical trials and passive surveillance (Hunt et al, 2015). Concern about adverse events associated with the administration of NSAIDs to small animals remains a barrier to their prescription by veterinary surgeons (Bell et al, 2014). The attitudes of pet owners regarding NSAID safety have not previously been reported in peer reviewed literature, but survey data has found a link between safety concerns and poor compliance (Zoetis Inc., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several surveys have assessed the attitudes and concerns of veterinarians, nurses and students with regard to the recognition, assessment and treatment of perioperative or chronic pain in small animals (Dohoo & Dohoo 1996a,b, 1998Capner et al 1999;Hellyer et al 1999;Lascelles et al 1999;Raekallio et al 2003;Hugonnard et al 2004;Williams et al 2005;Hewson et al 2006;Joubert 2006;Coleman & Slingsby 2007;Mich et al 2010;Keown et al 2011;Weber et al 2012;Bell et al 2014;Lorena et al 2014;Perret-Gentil et al 2014). However, none of these studies have specifically addressed canine abdominal visceral pain.…”
Section: Introductionmentioning
confidence: 99%